Do Artists Use Linear Perspective to Depict Visual Space?. (May 2014) - Pepperell, Robert; Haertel, Manuela
The question of how to accurately depict visual space has fascinated artists, architects, scientists, and philosophers for hundreds of years. Many have argued that linear perspective, which is based on well-understood laws of optics and geometry, is the correct way to record visual space. Others have argued that linear perspective projections fail to account for important features of visual experience, and have proposed various curvilinear, subjective, and hyperbolic forms of perspective instead. In this study we compare three sets of artistic depictions of real-world scenes with linear perspective versions (photographs) of the same scenes. They include a series of paintings made by one of the authors, a selection of landscape paintings by Paul Cézanne, and a set of drawings made as part of a controlled experiment by people with art training. When comparing the artworks with the photographs depicting the same visual space, we found consistent differences. In the artworks the part of the scene corresponding to the central visual field was enlarged compared with the photograph, and the part corresponding to the peripheral field was compressed. We consider a number of factors that could explain these results.